Detection of calreticulin as a candidate prognostic biomarker in invasive breast carcinoma from a biological scaffold-based 3D co-culture system - Sabaghpour Azarian, Mohammad Mehdi; Saad, Norazalina; Mohamad, Aslah; Rosli, Rozita (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Breast cancer is the most common cancer in women and the world’s second leading cause of death in women, after lung cancer. Calreticulin (CRT), an endoplasmic reticulum (ER) multipurpose protein, has been proposed as a potential biomarker for breast cancer. However, reports on the correlation between CRT expression and cell invasiveness in breast cancer micro-tissues are scarce. Thus, in the current study, we analyzed the potential correlation between CRT and invasiveness of breast cancer in a biological scaffold-based 3D co-culture system. Methods: MCF7, MDA-MB-231 and MCF-10A breast cell lines were co-cultured in a 3-dimensional (3D) system with MRC-5 lung fibroblast cell line in the cell density ratio of 3:1. Thereafter, calreticulin gene and protein expression levels were determined based on quantitative reverse transcription-polymerase chain reaction (RT-qPCR) and immunohistochemistry, respectively. Moreover, via RT-qPCR analysis, the gene expression levels of calreticulin-related candidate metastasis genes in breast cancer micro-tissues were carried out. Results: The results showed occasional foci of lumen-like morphology in the non-cancerous breast micro-tissues and the formation of solid clusters for breast cancer micro-tissues. Moreover, immunohistochemistry results revealed protein expression of calreticulin in non-cancerous and cancerous breast micro-tissues with cytoplasmic and nucleic acid localizations. It was found that PCMT1 and ER-α genes were significantly downregulated (p < 0.01) in invasive breast cancer micro-tissues. Conclusion: This study suggests that CRT and CRT-related candidate metastasis genes may potentially serve as prognostic biomarkers in invasive breast carcinoma.